THE USE OF INDONESIAN TEXTBOOKS IN THE EFL CLASS AS ALTERNATIVE ELT MATERIALS AT THE PRIMARY SCHOOLS IN INDONESIA - Y. E Budiyana; Yosi Ritonga; Antonius Suratno (Celt: A Journal of Culture, English Language Teaching & Literature, 2005)
The use of mother tongue in the EFL class is a controversial issue and the mother tongue seems to have no role to play. The idea of avoiding the mother tongue in language teaching is closely connected with the appearance of the direct method which emphasizes the use of English only in the English classroom. Many educators support the notion that within the ESL class, the only acceptable medium of instruction is English since it can be justified on pedagogical grounds. The use of mother tongue is considered as the teachers failure to teach English properly. However, the reality is different. As what Harbord (1987:351) says, there is an inevitable interaction between themother tongue and the target language, particularly in the EFL classroom. It is not a provocative way to use the mother tongue in ESL classroom but rather a justification for its limited use in certain situations The aims of our study are to find out the attitudes of both students and English teachers toward the use of Bahasa Indonesia in the English class, and if so how frequent and on what occasions it is used.